Optimasi Tween 80 dan Propilen Glikol dalam Self-Nanoemulsifying Drug Delivery System (SNEDDS) Minyak Atsiri Daun Kemangi (Ocimum basilicum) - Nofia Elisa Putri; Dwi Nurahmanto; Viddy Agustian Rosyidi (Pustaka Kesehatan, 2021)
Basil (Ocimum basilicum) is a plant from Lamiaceae family that has the potential for typhoid fever treatment. Basil essential oil is a hydrophobic compound being difficult to dissolve in the gastrointestinal tract. SNEDDS is one system that can solve this problem. The vital components of SNEDDS are surfactants and cosurfactants to increase the stability of the SNEDDS system by forming small droplets. This research determines the best composition of Tween 80 and Propylene glycol (PG), which can form nanoemulsion spontaneously in the gastrointestinal tract with a droplet size of nanometers. This research used a factorial design method to observed responses transmittance and emulsification time. Response transmittance and emulsification time then analyzed using Design Expert 11.0 to determine the optimum formula of SNEDDS basil essential oil. The optimum formula of SNEDDS basil essential oil obtained was a formula with a composition of 2.05 mL of Tween 80 and 1.35 mL of Propylene glycol. The optimum formula characterization test results showed a pH value of 7.01 ± 0.007; particle size 46.1 ± 0.61 nm; polydispersity index 0.46 ± 0.016. The antibacterial activity test optimum formula showed the ability to inhibit the growth of Salmonella typhi bacteria with an inhibition zone diameter of 20.50 ± 0.59 mm.